Does core training improve agility performance in soccer players with groin pain? a randomized, single-blind study. - Chaari, F.; Rahmani, A.; Peyrot, N.; Harrabi, M. A.; Fendri, T.; Rebai, H.; Boyas, S.; Sahli, S. (International Journal of Sports Physiology and Performance, 2025)
Context: Agility is crucial for soccer players, and core training can improve it. One study showed significant agility improvements after an intervention including core training for athletes with groin pain. However, it is unclear if these improvements resulted specifically from the core exercises or the entire program. Additionally, the study lacked a control group, making the findings inconclusive. Purpose: The current study aimed to explore the effect of core training, previously reported in the context of groin-pain rehabilitation, on agility performance in soccer players with groin pain. Methods: Twenty soccer players with groin pain volunteered to participate. They were randomly assigned to a core training group (n = 10) and a control group (n = 10). Before and immediately after that period, agility performance (T test and Edgren Side Step Test) and self-reported outcomes (Copenhagen Hip and Groin Outcome Score) were assessed in both groups. Results: No significant session × group interaction was observed in agility T test (F = 2.55; P = .12; n²p = .12) and Edgren Side Step Test (F = 3.18; P = .09; n²p = .15) performances. Besides, Copenhagen Hip and Groin Outcome scores showed significant improvements (P = .007 to <.001) in the core training group following the 12 weeks of core training and compared with the control group. Conclusion: The results showed that soccer players with groin pain who received or did not receive core training showed similar agility performance. However, significant improvements in self-reported outcomes were observed in soccer players compared with the control group. Clinicians and coaches should therefore consider core training when designing training and rehabilitation programs for this population to enhance recovery.